Changes in the market structure and risk management of Bitcoin and its forked coins - Kong, Xiaolin; Ma, Chaoqun; Ren, Yi-Shuai; Narayan, Seema; Nguyen, Thong Trung; Baltas, Konstantinos (Research in international business and finance, 2023)
Inconsistency of consensus results in blockchain forks, which create a new financial risk. After filtering out Bitcoin’s linear, nonlinear, and lag impacts on forked coins, this study employs a bottom-up hierarchical clustering algorithm to examine the logarithmic return series for Bitcoin and its 14 forked coins from 2018 to 2021. The results indicate that the market for forked coins can be divided into three clusters: SegWit-supported forked coins, mature forked coins, and the latest forked coins. Bitcoin and the mature forked coins form a cluster, and its performance is superior to others. Although Bitcoin’s return significantly affects that of its forked coins, it does not affect the market structure. Furthermore, this study provides references for risk aversion among investors in forked coins and presents macro-level information for cryptocurrency market authorities. [Display omitted] •This study examines the market structure of Bitcoin and its forked coins.•We use the bottom-up hierarchical clustering algorithm to divide Bitcoin and its forked coins into three clusters.•Although Bitcoin has a substantial effect on the returns of forked coins, it has no effect on their market structure.•We address how to avoid the potential financial dangers associated with forked coins.